Adam smith and the origins of american enterprise : how america's industrial success was forged by the timely ideas of a brilliant scots economist - Smith, Roy C. ([S.l.] : Truman Talley Books, 2002)
Adam Smith was a Scottish professor of moral philosophy. He published his classic The Wealth of Nations in 1776, the year the American Revolution began. Smith became widely known for his ideas of free markets, laissez-faire commerce, and the "invisible hand." Yet English politicians, landed gentry, and the nobility paid little attention and enacted none of Smith's suggested reforms. The American colonies, however, began their existence as an independent nation in 1781 with no money, no industry, no banks, and deep in debt. The Founding Fathers-particularly Alexander Hamilton, James Madison, and Benjamin Franklin-turned to the ideas of Adam Smith to create and jump-start an economic system for America with both immediate and long-sustained results. This little-known but vital part of U.S. history is now revealed in Roy C. Smith's highly readable new book.
Keywords: Economic history; Free enterprise; Smith, Adam, 1723-1790; United States